Analisis Tingkat Plagiarisme Terhadap Karya Ilmiah Jurnal Mahasiswa Perpustakaan dan Sains Informasi Universitas YARSI Jakarta Tahun 2021-2022 dengan Software Turnitin - Ario Adi Prakoso; Nurul Fadilah; Aya Yahya Maulana (Jurnal Pustaka Ilmiah, 2024)
The issue of plagiarism in higher education has received slightly firmer attention from Indonesian citizens. Apart from the academic community, the government also sends scientific understanding to the educated. This study aims to analyze the level of similarity index of scientific papers of library and information science student journals in 2021-2022 using Turnitin software. This research applies quantitative research methods with a descriptive approach and uses data collection techniques in the form of documentation studies. The population in this study is the scientific journal work of PDSI students at YARSI University in 2021-2022. The sampling technique uses a total sample, namely by taking all existing data. The samples taken amounted to 60 objects. The results showed that the search sources in the scientific work of library and information science student journals in 2021-2022 were divided into three, namely internet sources, publications, and student papers. Based on the average calculation, there was an increase of 0.23% in 2021 as much as 24.15% to 24.38% in 2022, the results of the 2021 Analysis of Internet Source percentage 53.16%, publications percentage 25.61%, and student papers percentage 21.23%. Meanwhile, the results of the 2022 analysis, namely the internet source percentage of 47.77%, publications percentage of 25.79%, and student papers percentage of 26.44%, can be concluded that plagiarism in students has increased because the use of Turnitin software has not been utilized properly by students.